Pengaruh Motivasi, Kepemimpinan Dan Budaya Organisasi Terhadap Loyalitas Anggoota Himpunan Pengusaha Muda Di Kota Malang - Mufticha, Mufticha; Khalikussabir, Khalikussabir; Amin, Muh Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of motivation, leadership, and organizational culture on the loyalty of members of the Indonesian Young Entrepreneurs Association (HIPMI) in Malang City. The research background is based on the crucial role of member loyalty in supporting organizational growth and sustainability, especially in the MSME sector, which is the backbone of the regional economy. This research uses a quantitative approach with a survey method among HIPMI Malang City members. Data were collected through questionnaires and analyzed using multiple linear regression to examine the simultaneous and partial effects of the independent variables on member loyalty. The results show that motivation, leadership, and organizational culture simultaneously have a significant effect on member loyalty. Partially, all three variables also make a positive contribution to loyalty. These findings emphasize the importance of synergy between motivation, leadership, and organizational culture in building member loyalty, which in turn can enhance organizational performance and competitiveness. This research provides practical implications for organizational management to strengthen these aspects to maintain and improve member loyalty.  Keywords: Motivation, Leadership, Organizational culture, Member loyalty, HIPMI, MSMEs.